PENGARUH VIDEO DALAM PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP PENINGKATAN SIKAP POSITIF PENGELOLAAN LINGKUNGAN SISWA SMP - Arum Sekar Melati; Ratini; Handoko Santoso (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2024)
This research aims to test whether there is an effect of learning using video in PBL on increasing positive attitudes towards environmental management for students of SMP Negeri 1 Way Bungur. The research method uses a qualitative research approach with the research design being a one-group pretest-posttest design. This research was conducted at SMP Negeri 1 Way Bungur with the research population being class VIII students. This research sample consists of one class with a total sample of 28 respondents. The instrument in this research used a positive attitude questionnaire with a scoring scale of 1-4. The results of this study indicate that there is an effect of video learning in PBL on managing positive attitudes towards environmental management with a significance value of 0.000 <0.05. The contribution to improving attitudes was 88.1%. The results of the study also showed that there was a positive increase in students' attitudes towards environmental management as evidenced by the overall positive gain scores.